IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 53 TAHUN 2010 TERKAIT DENGAN PENINGKATAN DISIPLIN KINERJA PERANGKAT KELURAHAN GUNA MENINGKATKAN PELAYANAN MASYARAKAT - Erlambang, Firda Pambudi; Suranto, Suranto (Res Publica: Jurnal Hukum Kebijakan Publik, 2020)
This study analyzes and examines the implementation of Government Regulation Number 53 Year 2010 related to increasing discipline to improve community services in Jantiharjo Village Karanganyar District Karanganyar Regency. This research is an empirical research conducted by processing primary and secondary data. Primary data obtained by conducting interviews while secondary data obtained by conducting library research related to employee discipline research. This research shows that there are several devices that require discipline in working hours, so that greater efforts are needed for the realization of good, effective, efficient community services, so that the goal of creating good governance will be maximally implemented.